Antenatal care behavior as a risk factor of nutritional anemia among pregnant women at South Denpasar II Public Health Centre, 2012 - Made Dwi Hendrayani; Anak Agung Sagung Sawitri; I Nyoman Mangku Karmaya (Public Health and Preventive Medicine Archive, 2013)
The South Denpasar II Public Health Centre has the highest reported nutritional anemia among pregnant women (57,4%) in the year 2011-2012. Nutritional anemia increased the risk of maternal and perinatal mortality, prematurity and low birth weight. This case control study aimed to identify the relationship between antenatal care (ANC) behaviour and nutritional anemia. The study involved 69 cases and 69 controls which taken from pregnant women records April to August 2012 by using a quota sampling. Cases were those with Hb Sahli levels <11 gr/dl, whereas those with Hb Sahli levels ≥11 were used as controls. Demographic characteristics, gestational age, parity, IUD use and ANC patterns were obtained by structured interviews and observations. ANC patterns which was evaluated from frequency and time of ANC and Fe tablets consumption were categorised as sufficient and insufficient. Data were analysed using univariate, bivariate (crude OR) and logistic regression for adjusted OR. Most women were aged 20-35 and had a low level of education, with gestational age >1st trimester, a parity of 1-3, and time window between births <2 years. Gestational age >1st trimester had 5.17 greater risk of nutritional anemia (95%CI: 1.66-16.06). Insufficient ANC behaviour increased risk of nutritional anemia as many as 23.29 (95%CI: 7.49-72.33) and 9.85 for insufficient Fe tablets consumption (95%CI: 3.27-29.68). Most of these women consumed less than <30 Fe tablets in the last month. Age, time between births, parity, family income, level of education, nutritional status and history of IUD use were proven not as risk factors. An early approach to newly couples, sekaa teruna teruni and senior high school students is needed to be targeted in regard to information of ANC. A more intensive surveillance is also needed to monitor Fe tablets consumption.